Temporal trends and disparities of population attributable fractions of modifiable risk factors for dementia in China: a time-series study of the China health and retirement longitudinal study (2011-2018)Research in context - Shanquan Chen; Xi Chen; Xiaohui Hou; Hai Fang; Gordon G. Liu; Lijing L. Yan (Elsevier, 2024)
Summary: Background: In China, dementia poses a significant public health challenge, exacerbated by an ageing population and lifestyle changes. This study assesses the temporal trends and disparities in the population-attributable fractions (PAFs) of modifiable risk factors (MRFs) for new-onset dementia from 2011 to 2018. Methods: We used data from the China Health and Retirement Longitudinal Study (CHARLS), covering 75,214 person-waves. We calculated PAFs for 12 MRFs identified by the Lancet Commission (including six early-to mid-life factors and six late-life factors). We also determined the individual weighted PAFs (IW-PAFs) for each risk factor. Subgroup analyses were conducted by sex, socio-economic status (SES), and geographic location. Findings: The overall PAF for dementia MRFs had a slight increase from 45.36% in 2011 to 52.46% in 2018, yet this change wasn't statistically significant. During 2011-2018, the most contributing modifiable risk was low education (average IW-PAF 11.3%), followed by depression, hypertension, smoking, and physical inactivity. Over the eight-year period, IW-PAFs for risk factors like low education, hypertension, hearing loss, smoking, and air pollution showed decreasing trends, while others increased, but none of these changes were statistically significant. Sex-specific analysis revealed higher IW-PAFs for traumatic brain injury (TBI), social isolation, and depression in women, and for alcohol and smoking in men. The decline in IW-PAF for men's hearing loss were significant. Lower-income individuals had higher overall MRF PAFs, largely due to later-life factors like depression. Early-life factors, such as TBI and low education, also contributed to SES disparities. Rural areas reported higher overall MRF PAFs, driven by factors like depression, low education, and hearing loss. The study also found that the gap in MRF PAFs across different SES groups or regions either remained constant or increased over the study period. Interpretation: The study reveals a slight but non-significant increase in dementia's MRF PAF in China, underscoring the persistent relevance of these risk factors. The findings highlight the need for targeted public health strategies, considering the demographic and regional differences, to effectively tackle and reduce dementia risk in China's diverse population. Funding: This work was supported by the PKU Young Scholarship in Global Health and Development.